Catherine Travis. Discourse markers in colombian spanish. A study in polisemy - Rojas Gallardo, Darío (Boletín de Filología, 2008)
CATHERINE TRAVIS. Discourse markers in colombian spanish. A study in polisemy. Mouton de Gruyter: Berlin - New York. 2005, 327 páginas.